Global Wheat Production 2018
DOI: 10.5772/intechopen.76154
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Sensitivity to Nitrogen Supply under Different Climatic Conditions

Abstract: With the projection of the Earth's population reaching eight billion in coming years and nine billion by 2050 which means increasing demand for food. Wheat (Triticum aestivum L.) is the main important and strategic cereal crop for feeding the majority of world's populations. Scientific forecasts predict that wheat production in the future will be affected by climate change and will decrease on the global level. To reduce these risks, the impact of climate change mitigation strategies and management systems for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Future research may explore potential differences among radish genotypes to accumulate Cd as one of sustainable approaches for utilising land with elevated Cd concentration in soil [15] and lowering the risk of toxic Cd entering into our food chain. Traditional breeding techniques in combination with transgenic approaches have been highlighted as a promising strategy for improving crop food/feed production in certain environmentally constrained conditions such as elevated Cd concentration in soil [4,5,15] and increased salinity [46]. For instance, Yu et al [47] identified 30 rice cultivars (among 43 tested) that maintained Cd concentration in grain within the limits safe for human consumption when grown on Cd-contaminated soil (1.75 mg Cd/kg soil).…”
Section: Resultsmentioning
confidence: 99%
“…Future research may explore potential differences among radish genotypes to accumulate Cd as one of sustainable approaches for utilising land with elevated Cd concentration in soil [15] and lowering the risk of toxic Cd entering into our food chain. Traditional breeding techniques in combination with transgenic approaches have been highlighted as a promising strategy for improving crop food/feed production in certain environmentally constrained conditions such as elevated Cd concentration in soil [4,5,15] and increased salinity [46]. For instance, Yu et al [47] identified 30 rice cultivars (among 43 tested) that maintained Cd concentration in grain within the limits safe for human consumption when grown on Cd-contaminated soil (1.75 mg Cd/kg soil).…”
Section: Resultsmentioning
confidence: 99%
“…In the context of increasingly important climate change, such production will presumably encounter more and more stressful conditions (i.e., plant water stress). In order to maintain the productivity, drought-and heat-tolerant crops/cultivars/hybrids must become the product of choice, as must the application of techniques to maintain the soil moisture by reducing evaporation [27,28]. More precisely, evaporation occurs when moist soil is exposed to the atmosphere.…”
Section: Selection Of Crops and Growing Techniques In Agricultural Armentioning
confidence: 99%
“…However, as is often observed, applying the optimal N concentration did not result in a correspondingly high yield. One reason is the imbalanced status of remaining nutrients responsible for the N economy during the grain-filling period [21].…”
Section: Introductionmentioning
confidence: 99%